KEPEMIMPINAN PEMERINTAHAN DALAM MEMPERBAIKI JALAN DI KABUPATEN SIMALUNGUN PADA TAHUN 2021 - Dwi Fadillah Nimas Utari; Hasanuddin ' (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Government leadership in this study is the ability of the Simalungun Regency Government to repair roads. The Simalungun Regency Government in 2021 has a program that distinguishes its leadership from the leadership of the previous Regent, namely the